Analysis Of The Application Of Government Accounting Standards To Fixed Assets And Its Impact On Audit Opinions - Chendy Martya; Erwin Febriansyah; Muliawati Muliawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to explain the causes behind the analysis of the implementation of Government Accounting Standards, Fixed Asset Reporting, and Internal Control Systems, and their implications for the audit opinion on the financial statements of the Kubu Raya Regency Government. This research adopts a qualitative approach. Data collection was conducted through interviews with the Head of the Accounting and Reporting Division of the Regional Financial and Asset Management Agency. The findings reveal that the application of government accounting standards in the financial audit opinion issued by the Audit Board of Indonesia (BPK), particularly in the area of asset recognition, remains problematic. Several assets have not yet been recognized due to the absence of ownership documentation, unrecorded outstanding local tax receivables, errors in budget planning, incomplete ownership records, and insufficient detail in the recording of fixed asset specifications in the inventory cards. The Regional Inspectorate and the Financial and Development Supervisory Agency, as the Government Internal Supervisory Apparatus (APIP), are encouraged to enhance oversight and provide assistance to the local government in implementing Government Accounting Standards (SAP), fixed asset governance, and the Integrity Assessment Survey. Strengthening these areas is expected to minimize findings during financial audits conducted by the Audit Board of Indonesia.